2013
DOI: 10.4236/jbise.2013.64054
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental biology in one<br>—A symposium in honour of Professor Kuo-Chen Chou’s 50th anniversary and Professor Richard Giegé’s 40th anniversary of their scientific careers

Abstract: It has been a dream that theoretical biology can be extensively applied in experimental biology to accelerate the understanding of the sophiscated movements in living organisms. A brave assay and an excellent example were represented by enzymology, in which the well-established physico-chemistry is used to describe, to fit, to predict and to improve enzyme reactions. Before the modern bioinformatics, the developments of the combination of theoretical biology and experimental biology have been mainly limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(34 citation statements)
references
References 91 publications
0
34
0
Order By: Relevance
“…Since user-friendly and publicly accessible web-servers represent the future direction for developing practically more useful models, simulated methods, or predictors (Chou and Shen, 2009;Lin and Lapointe, 2013), we shall make efforts in our future work to provide a web-server for the method presented in this paper. Table 5 Comparison of our achieved results (%) with the similar studies found in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Since user-friendly and publicly accessible web-servers represent the future direction for developing practically more useful models, simulated methods, or predictors (Chou and Shen, 2009;Lin and Lapointe, 2013), we shall make efforts in our future work to provide a web-server for the method presented in this paper. Table 5 Comparison of our achieved results (%) with the similar studies found in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Many marvellous biological functions in proteins and DNA and their profound dynamic mechanisms, such as switch between active and inactive states [46], cooperative effects [47], allosteric transition [48,49], intercalation of drugs into DNA [50] and assembly of microtubules [51], can be revealed by studying their internal motions, as elaborated in a comprehensive review and summarized in a recent paper [52,53] as well as a Wikipedia article at http://en.wikipedia.org/wiki/Low-frequency_collective_ motion_in_proteins_and_DNA. Likewise, to really understand the action mechanism of receptor-ligand or proteinprotein binding, we should consider not only the static structures concerned but also the dynamical information obtained by simulating their internal motions or dynamic process.…”
Section: Simulationmentioning
confidence: 99%
“…Since user-friendly and publicly accessible web-servers represent the future direction for developing practically more useful prediction methods or models Lin and Lapointe, 2013), we plan to provide a web-server for our method as done in (Liu et al, 2014;Qiu et al, 2014;Guo et al, 2014;Ding et al, 2014;Xu et al, 2014) in our future work. Table 6 Comparison between TLCF n with other related papers in terms of prediction accuracy.…”
Section: Resultsmentioning
confidence: 99%